Down the drain: The dynamic interplay of governance adjustments addressing setbacks in large public–private projects - Fang, F.; van der Valk, W.; Vos, B.; Akkermans, H. A. (Journal of Operations Management, 2024)
AbstractLarge government projects involving public–private collaborations inherently suffer from setbacks such as delays, cost overruns, or failure to meet contracted performance. Such setbacks may effectively be addressed through adjustments to contractual and relational governance; yet to date, the dynamics of governance adjustments and their interplay in addressing setbacks is not well understood. This research presents a dynamic theory of how parties can effectively address project setbacks through adjustments to contractual and relational governance. The dynamic theory was generated using longitudinal case data from two large public–private projects in the Netherlands that faced comparable project setbacks but deployed opposing governance adjustments, leading to drastically different project outcomes (i.e., collapse vs. recovery). This theory was then elaborated through two more cases and evidence from the literature. A system dynamics simulation model was then built that reproduces the different governance adjustments and outcomes observed in the four projects and serves to extend theory building. The refined theory not only shows under what conditions adjustments to contractual or relational governance are most effective, but also that governance adjustment interplay may trigger unintended side effects. As such, the theory explains why the careful balancing of governance adjustments is critical to project outcomes.